2006
DOI: 10.1088/0953-8984/18/48/011
|View full text |Cite
|
Sign up to set email alerts
|

Composition and temperature dependence of the thermoelectric power of Ni2+xMn1−xGa alloys

Abstract: Abstract. The thermoelectric power (TEP) measurements have been carried out to investigate the changes in the electronic structure associated with the intermartensitic and martensitic transitions in Ni 2+x Mn 1−x Ga (0 ≤ x ≤ 0.19). The samples have been characterized by a.c. magnetic susceptibility measurements. The correlation between the TEP and the microstructural changes sensitive to the increasing Ni content in Ni 2+x Mn 1−x Ga has been investigated. The changes in the density of states as reflected in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Besides the signatures associated with increasing e/a, and those ascribed to a typical ferromagnetic metal (like TEP minima), we observe almost constant value of TEP over a wide range in temperature in the martensitic phase. This change occurs as a result of nesting vectors formed due to differently modulated crystal structures in the martensitic phase causing weak localization of conduction electrons, as described earlier [6][7] . The highlight of TEP measurements in Ni-Mn-Ga is the slope of TEP that changes quite sharply in going from Ni 2 MnGa to Ni 2.19 Mn 0.81 Ga.…”
Section: Resultsmentioning
confidence: 82%
“…Besides the signatures associated with increasing e/a, and those ascribed to a typical ferromagnetic metal (like TEP minima), we observe almost constant value of TEP over a wide range in temperature in the martensitic phase. This change occurs as a result of nesting vectors formed due to differently modulated crystal structures in the martensitic phase causing weak localization of conduction electrons, as described earlier [6][7] . The highlight of TEP measurements in Ni-Mn-Ga is the slope of TEP that changes quite sharply in going from Ni 2 MnGa to Ni 2.19 Mn 0.81 Ga.…”
Section: Resultsmentioning
confidence: 82%
“…[9][10][11] While a considerable amount of experimental results is available in the literature on the magnetic, structural and electrical properties of FSM alloys, 12 there are relatively very few reports on the temperature and magnetic field dependencies of the thermal transport properties. [13][14][15][16][17][18] Thermal transport data on Ni-Mn-Ga FSM alloys show distinct changes across the T C and the MST-AST transitions. [14][15][16][17] Considerable changes in the thermoelectric power ͑Seebeck coefficient͒ are observed in the FSM alloy Ni 50 Mn 36 Sn 14 in presence of magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Thermal transport data on Ni-Mn-Ga FSM alloys show distinct changes across the T C and the MST-AST transitions. [14][15][16][17] Considerable changes in the thermoelectric power ͑Seebeck coefficient͒ are observed in the FSM alloy Ni 50 Mn 36 Sn 14 in presence of magnetic field. 18 In Ni-Mn-In system, Zhang et al, have reported a considerable change in thermal conductivity of Ni 50 Mn 33.7 In 16.3 alloy in presence of magnetic field.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations